First-line treatment of ovarian cancer FIGO stages IIb–IV with paclitaxel/epirubicin/carboplatin versus paclitaxel/carboplatin. (1st October 2003) - Kristensen, G. B.; Vergote, I.; Stuart, G.; Del Campo, J. M.; Kaern, J.; Lopez, A. B.; Eisenhauer, E.; Aavall-Lundquist, E.; Ridderheim, M.; Havsteen, H.; Mirza, M. R.; Scheistroen, M.; et al.
Abstract : The objective of this study was to compare the safety and efficacy of carboplatin plus epirubicin and paclitaxel (TEC) to carboplatin and paclitaxel (TC), in the treatment of epithelial ovarian, peritoneal, or tubal carcinoma. Between March 1999 and August 2001, 887 patients were randomized to receive six to nine cycles of paclitaxel (175 mg/m 2, 3 h intravenously) followed by carboplatin (AUC 5, Calvert formula) with or without epirubicin (75 mg/m 2 intravenously prior to paclitaxel), on a 3-weekly schedule. The primary endpoint was progression-free survival. Demographic information: Residual disease <1 cm was reported on 41% of patients. At the end of treatment, 65% in the TEC and 55% in the TC arm had achieved a clinical complete response, and 18 and 25% a clinical partial response resulting in an overall response rate of 83% in the TEC and 80% in the TC arm, whereas 7 and 9% had progressive disease, respectively. The three-drug combination produced a markedly higher myelotoxicity, resulting in a higher frequency of febrile neutropenia (12.5% of the TEC and 1.5% of the TC patients) and a higher number of dose reductions and treatment delays. Cycle prolongation above seven days was seen in 7 and 5% of cycles in the TEC and TC arm, respectively. Stomatitis ≥ grade 3 was also higher with TEC (4% TEC and 0.5% TC). Reductions in left ventricular ejection fraction of more than 15% after six courses were slightly more common with the TEC regimen (3% versus 1.5%), but the difference was not statistically significant ( P = 0.2). In conclusion, treatment with the TEC combination produced a higher rate of complete responses than treatment with the TC combination. Toxicity was manageable. Long-term survival data are awaited.